Świadectwa kultury prawnej w Polsce do 1320 roku - Lis, Artur (Przegląd Prawno-Ekonomiczny, 2013)
Streszczenie dostępnie wyłącznie w języku angielskim: The source of the knowledge of the former Piast Polish law are Liber fundationis claustri Sanctae Marie in Heinrichow i.e. The Book of Henryków and The Book of Elbląg – The Oldest Collection of Polish Laws. The first is not a list of rights, but gives a description of its operation, in addition to accurately present the development of the property of the monastery, gives information about the then almost to the ground each groups of her keepers. The Book of Elbląg is a list of private accomplished by an unknown writer. The Chronica Polonorum by Gallus Anonymus and The Chronica Polonorum by Vincentius Kadłubek are narrative sources. Chronicles are not only fundamental historical sources but also witness the Piast Polish legal culture.